STRATEGICITY AS A BASIC PRINCIPLE OF PROFESSIONAL AND PEDAGOGICAL ACTIVITY - Olha O. Lilik (Alfred Nobel University Publisher, 2020)
The author of this article characterizes the strategicity as a basic principle of professional and pedagogical activity, in particular, it is substantiated that strategy is a partial manifestation of strategicity as a more general complex phenomenon. It is accepted that within the framework of professional and pedagogical activity strategy can be considered as a kind of regulated mental education, which contributes to the effective solution of personal and professional tasks on the basis of actualization of available knowledge, skills and experience. It is substantiated that the process of strategy formation should be reflected within the triad: problem - solution - strategy. It is proved that the prerequisite for the formation of strategies in practice is the tendency to use the same type of mental actions, techniques, manifestations of basic mental operations and ways of solving problems. It was found that the strategic organization of professional and pedagogical activities is based on the idea of the unity of personal and procedural spheres of this activity. Specific features of strategicity are identified, such as: purposefulness, permanence, discreteness, cyclicity and phasing, reversibility, operability, rotation, combinatoriality, selectivity, aggressiveness, adaptability, integrativeness, emergence, limitedness, etc., motive. The article defines the sequence according to which individual components are transformed into a strategy through a complex system of relationships. It all starts with the awareness of the professional task and the emergence of a motive for its implementation, then there is a definition of the scope of professional activity, within which you want to perform the task, and the parameters of its consistent implementation. This is followed by a purposeful construction of an internal action plan, ideas, programs, selection of the desired results and specification of the specific goal, resulting in certain tactical actions that were planned in previous stages, and monitoring their performance, and, as a result, recording positive results of the strategy and evaluating one's own activities through self-reflection. It was found that strategies for solving professional problems within pedagogical activities are divided into algorithmic and heuristic. The algorithmic strategy is based on a certain algorithm as a set of rules that provide a single correct solution. Heuristic strategies do not give confidence in achieving a positive result, as they involve some creative independent search process, but they are much more important for studying the behavior of the teacher in solving a professional problem than an algorithmic approach. It is proved that the formation of strategy as a professional and personal trait of a teacher will help increase the level of formation of his professional competencies, stimulate further development and improvement